Optimizing Marketing Red Ginger Drink Products as an Effort to Increase Income - Sunduz, Siti; Rosidin, Cecep; Mulyana, Eldi; Dahlena, Alni (Entrepreneurship Faculty, Universitas Garut, 2024)
The development of the spread of the Covid-19 pandemic in West Java, which is increasingly becoming a health problem, has an impact on various sectors of people's lives. Where this disease must still be watched out for because the rate of spread is relatively fast, thus causing a higher mortality rate that cannot be ignored. The process of developing the Covid-19 pandemic in the West Java region, including Garut regency, is quite natural, making people need to increase their immunity, in addition to implementing the rules on health protocols. In an effort to increase the body's immunity, the public can consume foods that are in accordance with health recommendations. One of the herbal drinks that can increase the body's immunity is the Red Ginger drink. Red is an herbal product from local resident's agriculture in an effort to increase body immunity during the Covid-19 pandemic. The research method used in this study is a qualitative method through case studies and literature reviews. The results of this study indicate that; (1) Youth Organizations in Garut regency play a very important role in achieving Red Ginger agricultural products which are managed into herbal drinks to increase immunity of the community during the Covid-19 pandemic, (2) Karang Taruna Garut Regency play an active role in distributing Red Ginger drinks but has not optimally until only technology such as social media or media partners, (3) The activity of managing Red Ginger as a herbal drink by Karang Taruna, Garut Regency, has become an alternative driving force for the economy during the Covid-19 pandemic for farmers and foster and entrepreneurial spirit for the youth.